Walka o spadek. Anna Jagiellonka i Podlasie w latach 1572–1581 - Kalinowski, Emil (1988– ) (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
Under Zygmunt August’s will, after his death in 1572, his sister Anna inherited extensive land holdings in Podlasie, as well as movable property from her late brother, deposited in the Podlasie town of Tykocin. Since the beginning of the interregnum, however, she faced the reluctance of the Polish—Lithuanian noble elite to uphold the bequest in her favour. Finally, before her coronationin1576, she relinquished her inheritance in exchange for the compensation promised by her husband, Stephen Báthory. This was only granted to her in 1580–1581, although she already received income from part of the inherited property in 1574–1575.
p. 105-142
Summary in English.
Keywords: Anna Jagiellon; Zygmunt August; Podlasie; interregnum; inheritance; Sigismund II Augustus, King of Poland, (1520-1572); Anna Jagiellon (Queen of Poland; 1523-1596); interregnum - Poland - 16th c.